Comparison of efficiency of eutectic mixture and conventional solvents for the extraction of hydroxycinnamic acid derivatives from the herb of Satureja kitaibelii Wierzb. ex Heuff. (Lamiaceae) - Arsenijević, Jelena; Drobac, Milica; Slavkovska, Violeta; Dabetić, Nevena; Marcic, Christophe; Kovačević, Nada; Ražić, Slavica (Archives of Pharmacy, 2022)
Hydroxycinnamic acids (HCAs), such are dimeric rosmarinic acid (RA) and higher HCA oligomers, are important active constituents of Lamiaceae plants. It was found that herb of Satureja kitaibelii (Rtanj tea) contains substantial amounts of RA and HCA hexamer clinopodic acid O (CAO). In this work, we compared extracting efficiencies of conventional solvents and a deep eutectic solvent, composed of choline chloride and citric acid (ChCl:CitrA), for extraction of RA and CAO from Rtanj tea. Commercial Rtanj tea sample was extracted (1:10) by sonication (room temperature, 60 min) with aqueous ChCl:CitrA (35% and 65%), ethanol 50%, ethanol 96%, and water, as well as by previously optimized procedure (ethanol 46%, digestion 60 °C, 120 min). Contents of RA and CAO were determined by HPLC using RA as external standard. Extraction with ChCl:CitrA and 50% ethanol resulted in extracts rich in RA and CAO; RA concentrations in these extracts were uniform (848-873 µg/mL), while extraction of CAO was slightly more effective with ChCl:CitrA (1122-1131 µg/mL) than with 50% ethanol (925 µg/mL). These extracts contained significantly more of RA and CAO than the extract obtained under optimized conditions (666 µg/mL RA, 725 µg/mL CAO). Differently, 96% ethanol and water extracts contained substantially less RA (11-217 µg/mL) and CAO (4-10 µg/mL). Obtained results indicate potential of applied eutectic solvent in extraction of Rtanj tea, for purpose of both quality control and preparation of extracts with potential application in pharmaceutical, food or cosmetic industry, and are compliant with “green chemistry” and “green pharmacy” principles.